Intratumoral sustained release of resiquimod with ablative fractional laser induces efficacy in a cutaneous squamous cell carcinoma mouse model - Wiinberg, Martin; Melander, Fredrik; Lerche, Catharina M.; Andresen, Thomas L.; Olesen, Uffe H.; Haedersdal, Merete (Frontiers in Immunology, 2025)
IntroductionThe Toll-like receptor (TLR) 7/8 agonist resiquimod has shown promise for precancerous lesions of cutaneous squamous cell carcinoma (cSCC) but remains unexplored as a treatment for cSCC. Additionally, ablative fractional laser (AFL) has been shown to enhance the efficacy of TLR7 agonist in mouse tumor models. This study investigates the efficacy of intratumoral resiquimod formulated into a sustained-release gel (RSQ-gel) in a cSCC mouse model and compares RSQ-gel with topical imiquimod (IMQ) cream, a clinically approved TLR7 agonist. We further examine whether adjuvant AFL enhances the efficacy of RSQ-gel.MethodsA syngeneic transplanted cSCC mouse model was established using cells from a UVR-induced cSCC mouse model. The immunostimulatory effects of RSQ-gel were assessed by analyzing the expression of the activation marker CD86 on plasmacytoid dendritic cells (pDC) and cross-presenting conventional type I dendritic cells (XCR1+ cDC1) via flow cytometry. Tumor growth and survival outcomes were evaluated for RSQ-gel as monotherapy and in combination with AFL.ResultsRSQ-gel was associated with activation of pDCs and XCR1+ cDC1s in the tumor-draining lymph node, as indicated by higher expression of CD86 compared to IMQ (P< 0.0001, P = 0.00175, respectively). RSQ-gel monotherapy delayed tumor growth but did not prolong survival (P = 0.0651). However, combining RSQ-gel with AFL resulted in prolonged survival compared to AFL-treated and untreated mice (P = 0.0153, P = 0.0214, respectively). Weekly RSQ-gel treatment induced comparable efficacy to daily topical IMQ treatment.DiscussionRSQ-gel with AFL demonstrated significant antitumor efficacy in the cSCC mouse model. Local RSQ-gel combined with adjuvant AFL may offer a promising therapeutic approach for cSCC.